Chylous ascites after an H-graft interposition mesocaval shunt. Issue 7 (July 1982) - Reichen, J; Schaefer, J W
Abstract : A case of chylous ascites occurring after an emergency mesocaval shunt is reported. After an attempt at conservative management had failed, the patient was surgically explored. Although a lymphatic leak could not be identified, oversewing the retroperitoneum in the area of previous dissection and reinforcement with an omental pedicle was successful in preventing postoperative reaccumulation of chylous ascites. A review of the 26 reported cases of postoperative chylous ascites indicates a spontaneous resolution rate of 41% with non-operative management including low fat diet, paracenteses, and total parenteral nutrition. If conservative measures fail, surgical repair of the traumatised lymphatic bed has been successful.